If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -7 = 5x + 1 Reorder the terms: -7 + 2x = 5x + 1 Reorder the terms: -7 + 2x = 1 + 5x Solving -7 + 2x = 1 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -7 + 2x + -5x = 1 + 5x + -5x Combine like terms: 2x + -5x = -3x -7 + -3x = 1 + 5x + -5x Combine like terms: 5x + -5x = 0 -7 + -3x = 1 + 0 -7 + -3x = 1 Add '7' to each side of the equation. -7 + 7 + -3x = 1 + 7 Combine like terms: -7 + 7 = 0 0 + -3x = 1 + 7 -3x = 1 + 7 Combine like terms: 1 + 7 = 8 -3x = 8 Divide each side by '-3'. x = -2.666666667 Simplifying x = -2.666666667
| -3b-15=12b+30 | | x^2+10x=75 | | 8x-4=9x+7 | | 8z-6=7z+16 | | 28x-140=0 | | .6x^2-4x-160=0 | | 8=-3u | | 8z-6=7z+6 | | 4+d=11 | | 48/1=a+7/6 | | 2x^2=-14x-20 | | 5x-10=-9x | | w^2-36=-64 | | 15x-35y+90=0 | | 3(4x-22)=78 | | A^2-8a-9=0 | | 12x^5y^2z^2-24x^4y^2z^2+12x^3y^2z^2= | | 86=29+y | | (x^2+10x)+y^2=0 | | 10-4n=26 | | 56a+90+58a=92 | | x^3-2x=0 | | x-3+x+x+5=33 | | 5+.5s=s | | 4m^2-25= | | 6x+28=10x | | 144b^2=36 | | 56=26x | | 7+x-9=103732 | | x^3+5x^2+4x-20=0 | | x^4+-8x^3+17x^2+-8x+16=0 | | X=7-4+3*0+1 |